microRNA 17/20 inhibits cellular invasion and tumor metastasis in breast cancer by heterotypic signaling - Yu, Zuoren (National Academy of Sciences, 2010)
microRNAs are thought to regulate tumor progression and invasion via direct interaction with target genes within cells. Here the microRNA17/20 cluster is shown to govern cellular migration and invasion of nearby cells via heterotypic secreted signals. microRNA17/20 abundance is reduced in highly invasive breast cancer cell lines and node-positive breast cancer specimens. Cell-conditioned medium from microRNA17/20–overexpressing noninvasive breast cancer cell MCF7 was sufficient to inhibit MDA-MB-231 cell migration and invasion through inhibiting secretion of a subset of cytokines, and suppressing plasminogen activation via inhibition of the secreted plasminogen activators (cytokeratin 8 and α-enolase). microRNA17/20 directly repressed IL-8 by targeting its 3′ UTR, and inhibited cytokeratin 8 via the cell cycle control protein cyclin D1. At variance with prior studies, these results demonstrated a unique mechanism of how the altered microRNA17/20 expression regulates cellular secretion and tumor microenvironment to control migration and invasion of neighboring cells in breast cancer. These findings not only reveal an antiinvasive function of miR-17/20 in breast cancer, but also identify a heterotypic secreted signal that mediates the microRNA regulation of tumor metastasis.